Model Implementasi Catur Asrama dalam Penguatan Resiliensi Sosial-Ekonomi Keluarga Hindu di Desa Krisik - Sukirno Hadi Raharjo; Ni Made Ayu Krisna Cahyadi (Jayapangus Press, 2026)
Hindu families in Krisik Village, Gandusari Subdistrict, Blitar Regency face complex socio-economic challenges, including changes in social patterns, limited economic resources, and low internalization of Hindu teachings in daily life practices. The gap between normative religious understanding and the community's socio-economic practices is evident in the implementation of Catur Asrama, a life stage system that regulates education, social responsibilities, and dharma-based economic activities. This study aims to formulate and analyze a model for implementing Catur Asrama to strengthen the socio-economic resilience of Hindu families in Krisik Village. A qualitative approach with a case study design was used, with data collected through in-depth interviews, participatory observation, and document studies. Informants were selected purposively, including religious leaders, administrators of religious organizations, Hindu educators, village officials, and local economic actors. Data analysis was conducted thematically through reduction, categorization, and the drawing of interpretative conclusions. The research results indicate that the implementation of Catur Asrama, particularly the Brahmacari and Gṛhastha phases, plays a central role in strengthening the socio-economic resilience of families. Brahmacari shapes characters with discipline, responsibility, and educational orientation that support future economic readiness, whereas Gṛhastha becomes the center of economic productivity through the reinforcement of a dharma-based work ethic, wise household management, and active participation in social networks and customary activities. The integration of spiritual values, social practices, and economic strategies strengthens community social capital and enhances family capacity to face economic pressures and social changes. The research conclusion affirms that Catur Asrama functions as an ethically-economic framework based on dharma that is effective, making religious values not only normative but also strategic in building economic independence, social solidarity, and the sustainability of Hindu families at the community level.